A comparison of optical properties of ZnO nanorods and ZnO nanotips for improving light absorption in rGO/ZnO nanostrctures - Fallahazad, Parisa; Sharifi, Mahsa; Naderi, Nima; Eshraghi, Mohamad Javad (Journal of Composites and Compounds, 2022)
In this study, two types of ZnO nanostructures (ZnO nanotips and ZnO nanorods) were synthesized through a chemical bath deposition (CBD) method. These two structures were then compared by optical and structural analyses. The result showed the significant effect of ammonia concentration and the preferential etchings along the c axis on the formation of ZnO nanotips (NTs). To improve the absorption, nanostructures were optimized by reflectance analysis. To enhance the optical properties of the optimized sample, reduced graphene oxide (rGO) layers were transferred on the ZnO NTs surface by the electrophoretic deposition (EPD) method. The deposition of rGO layers on ZnO NTs can increment the optical absorption over a wide range of frequencies. The reflectance results showed enhanced adsorption capacity in the case of rGO/ZnO NTs.